2024
DOI: 10.1038/s41467-024-46356-y
|View full text |Cite
|
Sign up to set email alerts
|

Biosensor and machine learning-aided engineering of an amaryllidaceae enzyme

Simon d’Oelsnitz,
Daniel J. Diaz,
Wantae Kim
et al.

Abstract: A major challenge to achieving industry-scale biomanufacturing of therapeutic alkaloids is the slow process of biocatalyst engineering. Amaryllidaceae alkaloids, such as the Alzheimer’s medication galantamine, are complex plant secondary metabolites with recognized therapeutic value. Due to their difficult synthesis they are regularly sourced by extraction and purification from the low-yielding daffodil Narcissus pseudonarcissus. Here, we propose an efficient biosensor-machine learning technology stack for bio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 60 publications
0
1
0
Order By: Relevance
“…This phenomenon increases the specific recognition signal, thereby improving the sensitivity of aptamer-based EABs markedly. 13 In order to pursue higher sensitivity and activity of aptamer-based EABs, a conductive medium is required between the aptamer and electrode to facilitate electron transfer of aptamer-based EABs.…”
Section: Set-based Electrochemical Biosensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon increases the specific recognition signal, thereby improving the sensitivity of aptamer-based EABs markedly. 13 In order to pursue higher sensitivity and activity of aptamer-based EABs, a conductive medium is required between the aptamer and electrode to facilitate electron transfer of aptamer-based EABs.…”
Section: Set-based Electrochemical Biosensorsmentioning
confidence: 99%
“…1). 10–14 The precise binding of biorecognition elements leads to interaction fluctuations, which can be subsequently captured by signal transducers and converted into discernible electrical impulses, fluorescence signals, thermal or acoustic signals. 15–17 In order to facilitate the conversion of interaction fluctuations into detectable signals, a variety of nano-functional materials, such as carbon-based materials, 18 metal nanoparticles, 19 MXenes, 20 metal–organic frameworks, 12 covalent organic frameworks, 21 and organic polymers, 22 have been used to manufacture electrochemical and fluorescent biosensors.…”
Section: Introductionmentioning
confidence: 99%
“…To improve upon this starting point, we mutations predicted by MūtCompute, a three-dimensional self-supervised, convolutional neural network, which were previously identied for an enzyme engineered to catalyze an asymmetric alkene hydroalkylation. [27][28][29] We found that mutating threonine 36 to aspartic acid (T36E), increased the yield to 78% with no change in the enantioselectivity of the transformation. Mutation of serine at position 118 to cystine (S118C) led to product formation in 86% yield.…”
mentioning
confidence: 94%
“…While ML tools can be integrated into engineering workflows, they often require extensive training datasets either from enzyme-specific reaction assays or non-structural genetic data. [ 27 – 32 ] Tailoring of extensive datasets for each specific enzyme still requires burdensome front-work from researchers. Thus, synergizing ML technologies with existing rational design strategies offers a low-barrier solution for identifying potentially beneficial mutations in an engineering campaign.…”
Section: Introductionmentioning
confidence: 99%